FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA GIZI KURANG PADA ANAK BALITA USIA 24-59 BULAN (STUDI DI WILAYAH KERJA PUSKESMAS HALMAHERA KOTA SEMARANG TAHUN 2017) - Arum, Rzky; Rahfiludin, M. Zen; Nugraheni, Sri Achadi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Data of surveilans nutritional Indonesian on 2016 mentioned percentage of moderately malnourished in Indonesia severally 11,1%, this grade identified that Indonesian belong to country with undernutrition (>5%). The aim of this research was to review factor who has connection with malnourished children aged 24-59 month at Halmahera local goverment clinic, Semarang city. This research using quantitative method with analytic descriptive and chase control design. Respondense of this research were 68 mom and children consist 34 chases and 34 control, and continued using chi-square test. Results of this research showed that mother’s education (CI= 0,616-6,139 ; OR= 1,944) was not correlate and was not a risk factor, mother’s knowledge (CI= 0,343-2,302 ;OR=0,889) was not correlate and was not a risk factor but a protective factor, infectious disease (CI= 0,431-2,950; OR= 1,128) was not correlate and was not a risk factor, toddlers caring pattern (CI= 0,305-2,048 ; OR= 0,790) was not correlate and was not a risk factor but a protective factor, total family member (CI= 0,639-4,851 ; OR= 1,833) was not correlate and was not a risk factor, economic status (CI=0,466-3,786 ; OR= 1,329) was not correlate and was not a risk factor, utilization of health service (CI= 0,229-4,373 ; OR= 1,000) was not correlate and was not a risk factor, Level of Energy Consumption (CI= 0,097-1,030 ; OR= 0,316) was not correlate and was not a risk factor but a protective factor, and Level of Protein Consumption (CI= 0,284-6,681 ; OR= 1,378) was not correlate and was not a risk factor. This research recommended mothers to keep maintaining toddler’s nutritional intake in order to increase toddler’s nutritional needs, and mothers were suggested to bring KMS so they could see the children’s development graphs.